Sismorcego: Usability Evaluation of an Offline Mobile Application for Surveillance of Sylvatic Rabies in the Amazon - Alves, André Vinicius Neves; Santos, Bradsson; Pinto, Lyanh Lopes; Lima, Pedro; Pontes, Paulo Andre Ignacio; Costa, SauloWilliam da Silva; Silva, Nailde de Paula; Abel, Isis; Seruffo, Marcos César da Rocha (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
The Amazon region faces severe logistical and climatic challenges that hinder the epidemiological surveillance of wild rabies. The traditional use of paper forms often results in delays in reporting and the loss of geographic tracking of outbreaks. This study presents Sismorcego, an offline-first mobile app developed to record and georeference bat attacks in areas without network connectivity. To assess the tool’s practical feasibility, the System Usability Scale method was applied to 42 Community Health Agents. The app obtained an average score of 74.80, with heuristic highlights for Efficiency (73.21) and Satisfaction (75.79). Statistical validation using the Wilcoxon test (p = 0.0006) confirmed that the system’s usability is significantly higher than the 68-point acceptability threshold. The results indicate that the transition to an offline digital solution is a viable strategy for overcoming geographic isolation, ensuring continuous and accurate monitoring of zoonoses in the Amazon.